Identifikasi Penyebab Kegagalan Potensial Pada Proses Produksi Menggunakan Metode Multi Attribute Failure Mode Analysis (MAFMA) - Wiwiek Fatmawati; Sukarno Budi Utomo; Riko Khaerul Anam (Program Studi Teknik Industri Universitas Setia Budi, 2024)
XYZ MSMEs engaged in convection screen printing recorded a fairly high level of product process defects that resulted in product defects with an average defect of 5%. Some of the causes of failure in the production process include images that are not clearly printed, images that are sit-inspired, inappropriate cuts, untidy seams, t-shirts that are stained with screen printing ink, and faded screen printing results. Efforts to reduce these various problems are carried out by identifying potential failures in the production process using the Multi Attribute Failure Mode Analysis (MAFMA) method. This method produces the highest alternative weight value so that it makes it easier to make action decisions. There is one most potential failure, namely untidy seams with a total value of 0.244. The improvement strategy is carried out by paying attention to the causes of potential failures by looking at influential factors, namely human, machine, material, method and environmental factors analyzed using fishbone diagrams. Operators who are not careful and in a hurry when working, the condition of sewing machines and screen printing presses that are poorly maintained, sewing thread materials and screen printing dyes that are inconsistent in quality, there are no SOPs for operators and an uncomfortable working environment that affects the quality of the sewing and screen printing results produced. Improvement proposals are made by conducting training for workers, performing scheduled machine maintenance, checking materials before the production process, selecting trusted suppliers, making SOPs for operators and regulating production room conditions so that operators are comfortable when working.